Erythema‐directed digital photography for the enhanced evaluation of topical treatments for acne vulgaris. Issue 3 (31st January 2018) - Micali, G.; Dall'Oglio, F.; Tedeschi, A.; Lacarrubba, F.
Abstract: Background: Erythema‐directed digital photography is a novel method for evaluating the efficacy and tolerability of topical acne treatments. Here, we describe three case reports in which erythema‐directed digital photography was used to evaluate acne before and after up to 12 weeks of treatment with clindamycin 1%/tretinoin 0.025% (Clin‐RA). Materials and methods: Erythema‐directed digital photography was used to evaluate acne in three patients with mild‐to‐moderate facial acne, two of whom had refused to continue previous topical acne treatment (benzoyl peroxide 5% and clindamycin 1%/benzoyl peroxide 5%) due to persistent irritation. Acne lesions and erythema were evaluated using standard clinical photography and erythema‐directed digital photography (VISIA‐CR ™ system) before and after 8‐12 weeks of treatment with Clin‐RA. Results: Erythema‐directed digital photography revealed background erythema from previous topical acne treatments that was not evident from standard clinical photographs and allowed a better visualization of both inflammatory and non‐inflammatory lesions. In all patients, there was a clear improvement in background erythema and a reduction in acne lesions following treatment with Clin‐RA. Conclusion: This study has demonstrated for the first time that erythema‐directed digital photography can enhance the evaluation of the efficacy and tolerability of topical acne treatments. These cases show that Clin‐RA was associated with improved efficacy and tolerability vs previous treatments with topical monotherapy (benzoyl peroxide 5%) or a topical fixed‐dose combination (clindamycin 1%/benzoyl peroxide 5%).